definition: |
(<>) :: Mod -> Mod -> Mod (Mod o1 a1) <> (Mod o2 a2) = Mod (o2 . o1) (a2 . a1) |
demand: |
arguments 1 2 |
deterministic: |
deterministic operation |
documentation: |
--- Combine two modifiers. |
failfree: |
(_, _) |
indeterministic: |
referentially transparent operation |
infix: |
no fixity defined |
iotype: |
{({Mod},{Mod}) |-> {Mod}} |
name: |
<> |
precedence: |
no precedence defined |
result-values: |
{Mod} |
signature: |
Mod -> Mod -> Mod |
solution-complete: |
operation might suspend on free variables |
terminating: |
yes |
totally-defined: |
reducible on all ground data terms |